Notes—A Note on “Preferences, Summation, and Social Welfare Functions” - Williams, Fred E. (Management Science, 1970)
A note on Fishburn, Peter C. 1969. Preferences, summation, and social welfare functions. Management Sci. 16(3, November) 179–186.